Antigenicity of Primary Endodontic Infection against Macrophages by the Levels of PGE(2) Production - Martinho, Frederico Canato [UNESP]; Maia Chiesa, Wanderson Miguel; Leite, Fabio R. M.; Cirelli, Joni Augusto [UNESP]; Gomes, Brenda P. F. A. (Elsevier B.V., 2011)
Introduction: Root canal contents are potent stimuli for proinflammatory cytokines involved in apical periodontitis. This study investigated target gram-negative bacterial species and endotoxins in primary endodontic infection with apical periodontitis, determined their antigenicity against macrophages through the levels of PGE(2), and evaluated their relationship with clinical findings. Methods: Samples were taken from 21 root canals with primary infection and apical periodontitis by using paper points. Polymerase chain reaction (165 rDNA) was used for bacterial detection and limulus amebocyte lysate assay for endotoxin measurement. Levels of prostaglandin E2 (PGE(2)) were measured by enzyme-linked immunosorbent assay (Duoset Kit; R&D, Minneapolis, MN). Results: Prevotella nigrescens (13/21), Fusobacterium nucleatum (6/21), and Porphyromonas endodontalis (6/21) were the most frequently observed species. A positive association was found between F nucleatum and P endodontalis (P < .05). A correlation was found between the number of gram-negative bacterial species and the levels of endotoxins, as well as PGE2 (P < .05). Higher levels of endotoxin were detected in teeth with exudation, whereas elevated levels of PGE(2) were found in teeth with tenderness to percussion and pain on palpation. Conclusions: Our findings imply an additive effect between the number of gram-negative bacterial species involved in endodontic infection regarding the induction of proinflammatory cytokine by macrophage cells. Moreover, teeth with clinical symptomatology were related to higher levels of endotoxins and PGE2 secretion. (J Endod 2011;37:602-607)
Keywords: Bacteria; endotoxin; macrophages; prostaglandin E2; root canal